Amériques transculturelles/ Transcultural Americas - Afef Benessaieh (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 2010)
Transculturalism is a new way of viewing culture that sees cultures not as separate islands, but as connected and interacting webs. The Americas in particular offer many examples of transcultural identities: Chicanos, Franco-Ontarians, Creoles, and second and third generation immigrants. Transcultural Americas explores these identities which create themselves in a space between sameness and difference.